Facts about Vitamin A - Nan C. Jensen; Linda B. Bobroff (EDIS, 2006)
Revised! FCS-8639, a 2-page fact sheet by Nan C. Jensen and Linda B. Bobroff, has been updated with new graphics. Published by the UF Department of Family Youth and Community Sciences, April 2006.